The Therapeutic Role of Ziziphus Extract on Liver Injury Induced by Electromagnetic Waves and Ionizing Radiation as Environmental Pollutants (Journal of Nuclear Technology in Applied Science, 2018)
This study shows to what extent treatment with Ziziphus mauri tiana Lam can ameliorate the hazards induced by exposing animals to  EMW with a frequency of 950 MHz and 4 Gy single dose of gamma  ionizing radiation in serum and liver tissue. Rats were segregated into  six groups control, EMW, whole body γ- irradiation, EMW followed by  γ- irradiation and EMW followed by Ziziphus extract then exposed to  γ- irradiation groups. Irradiation with 4 Gy γ- rays significantly increased  the levels of serum Alpha-Fetoprotein (AFP), Alanine Aminotransferase  (ALT) and Aspartate Aminotransferase (AST) activities; with substantial  reductions in liver glutathione peroxidase (GPx), while lipid peroxides  as malondialdehyde (MDA), nitric oxide (NO), Heat Shock Protein 70  (HSP 70), Nuclear Factor κB (NFkB) and tumor suppressor protein (P53)  levels significantly increased in liver tissue after EMW or ionizing radiation exposure. However, these effects became marked in all parameters  in Group 5 as compared either to Group 3 or 4. Interestingly, among  the tested parameters, ziziphus extract showed significant recovery in the  previous biochemical parameters. Ziziphus extract is effective antioxi dants and could be attenuate oxidative damages caused by electromag netic and ionizing radiation.
Keywords: Electromagnetic Waves; Ethanol Ziziphus Extract; Heat Shock Protein70; Environmental Pollutants